DNA Microarray Analysis of Differential Gene Expression in the Dorsal Root Ganglia of Four Different Neuropathic Pain Mouse Models - Yokoyama H; Hirai T; Nagata T; Enomoto M; Kaburagi H; Leiyo L; Motoyoshi T; Yoshii T; Okawa A; Yokota T (Journal of Pain Research, 2020)
Hiroyuki Yokoyama,1 Takashi Hirai,1 Tetsuya Nagata,2 Mitsuhiro Enomoto,1 Hidetoshi Kaburagi,1 Li Leiyo,1 Takayuki Motoyoshi,1 Toshitaka Yoshii,1 Atsushi Okawa,1 Takanori Yokota2 1Department of Orthopedic Surgery, Tokyo Medical and Dental University, Tokyo 113-8519, Japan; 2Department of Neurology and Neurological Science, Tokyo Medical and Dental University, Tokyo 113-8519, JapanCorrespondence: Takashi Hirai; Takanori Yokota Email Hirai.orth@tmd.ac.jp; tak-yokota.nuro@tmd.ac.jpPurpose: Pathological stimuli or injury to the peripheral nervous system can trigger neuropathic pain with common clinical features such as allodynia and hypersensitivity. Although various studies have identified molecules or genes related to neuropathic pain, the essential components are still unclear. Therefore, in this study, we investigated the molecular and genetic factors related to neuropathic pain.Methods: We extracted candidate genes in the dorsal root ganglion (DRG) from three nerve injury mouse models and a sham-operated model (sciatic nerve ligation and resection, sural nerve resection, spared nerve injury [SNI], and sham) using DNA microarray to elucidate the genes responsible for the neuropathic pain mechanism in the SNI model, which exhibits hypersensitivity in the hindpaw of the preserved sural nerve area. We eliminated as many biases as possible. We then focused on an upregulated endogenous vasopressin receptor and clarified whether it is closely associated with traumatic neuropathic pain using a knockout mouse and drug-mediated suppression of the gene.Results: Algorithm analysis of DNA microarray results identified 50 genes significantly upregulated in the DRG of the SNI model. Two independent genes—cyclin-dependent kinase-1 (CDK-1) and arginine vasopressin receptor 1A (V1a)—were subsequently identified as candidate SNI-specific genes in the DRG by quantitative PCR analysis. Administration of V1a agonist to wild-type SNI mice significantly alleviated neuropathic pain. However, V1a knockout mice did not exhibit higher hypersensitivity to mechanical stimulation than wild-type mice. In addition, V1a knockout mice showed similar pain behaviors after SNI to wild-type mice.Conclusion: Through the DNA microarray analysis of several neuropathic models, we detected specific genes related to chronic pain. In particular, our results suggest that V1a in the DRG may partially contribute to the mechanism of neuropathic pain.Keywords: neuropathic pain, arginine vasopressin 1a, peripheral nerve injury, dorsal root ganglion, microarray, molecular target